Performance Study of Reverse Osmosis Plants for Water Desalination in Bandar-Lengeh, Iran - Alireza Zirakrad; Seyed Jamalodin Hashemian; Mohammad Taghi Ghaneian (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: Reverse osmosis (RO) is best known for its use in desalination (removing the salt from seawater to get fresh water), but since the early 1970s it has also been used to purify fresh water for medical, industrial, and domestic applications. The aim of this research was the performance study of reverse osmosis plants for water desalination in Bandar-Lengeh, Iran. Materials and Methods: In this study the concentrations of a number of physical, chemical and biological quality parameters in raw and treated water of Bandar-Lengeh water Desalination Plants were determined and Performance of RO plants for seawater and costal groundwater desalination were studied. There are two desalination plants in Bandar-Lengeh. Water from these plants are used for municipal supply. Total production capacity of the two RO desalination plants is 8000 m3/d. Results: The results of this study showed average values of TDS, Sodium, Chloride, Sulfate, diatomaceous and Nematodes in seawater were 37749 mg/l; 9715 mg/l; 22020 mg/l; 3067 mg/l; 24337 N/100ml and 5 N/100ml and in treated water were 1233 mg/l; 436 mg/l; 710 mg/l; 58 mg/l, 0 N/100ml and 0 N/100ml, respectively. Also the results showed average values of TDS, Sodium, Chloride and Sulfate in coastal ground water were 37131 mg/l; 9303 mg/l; 21072 mg/l; 3745 mg/l; and in treated water were 687mg/l; 253 mg/l; 389 mg/l; 19 mg/l, respectively. Conclusion: The results showed the quality of feed water and pretreatment plays an extremely important role in operational problems such as fouling of RO systems.